+0  
 
0
240
1
avatar

i need some milk

Guest Jun 21, 2017

Best Answer 

 #1
avatar+87655 
+2

 

 

Using the property     a^m * a^n  =  a^(m + n) we have that

 

(-2)^-13 * (-2)^5  =   (-2)^(-13 + 5)   =  (-2)^(-8)  =  1 / (-2)^8  =  1 / 256

 

 

cool cool cool

CPhill  Jun 21, 2017
 #1
avatar+87655 
+2
Best Answer

 

 

Using the property     a^m * a^n  =  a^(m + n) we have that

 

(-2)^-13 * (-2)^5  =   (-2)^(-13 + 5)   =  (-2)^(-8)  =  1 / (-2)^8  =  1 / 256

 

 

cool cool cool

CPhill  Jun 21, 2017

17 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.